2013
DOI: 10.5194/bg-10-7739-2013
|View full text |Cite
|
Sign up to set email alerts
|

A fertile peatland forest does not constitute a major greenhouse gas sink

Abstract: Abstract. Afforestation has been proposed as a strategy to mitigate the often high greenhouse gas (GHG) emissions from agricultural soils with high organic matter content. However, the carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) fluxes after afforestation can be considerable, depending predominantly on site drainage and nutrient availability. Studies on the full GHG budget of afforested organic soils are scarce and hampered by the uncertainties associated with methodology. In this study we determined the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 92 publications
3
47
0
6
Order By: Relevance
“…Mostly, drained peatland forests are reported to be strong annual net CO 2 sinks (> −150 g C m −2 a −1 ). At some peatland forests sites the net CO 2 sink is entirely attributable to the carbon accumulation of the trees (Hargreaves et al, 2003;Meyer et al, 2013;von Arnold et al, 2005), but at other sites even the soil is a net CO 2 sink (Lohila et al, 2011;Minkkinen et al, 2002). However, for two drained peatland forests, of different age and different nutrient supply, Dunn et al (2007) and Lohila et al (2007) found an annual NEE close to zero (+84 and −58 g C m −2 a −1 ).…”
Section: Annual Co 2 Exchangementioning
confidence: 98%
See 1 more Smart Citation
“…Mostly, drained peatland forests are reported to be strong annual net CO 2 sinks (> −150 g C m −2 a −1 ). At some peatland forests sites the net CO 2 sink is entirely attributable to the carbon accumulation of the trees (Hargreaves et al, 2003;Meyer et al, 2013;von Arnold et al, 2005), but at other sites even the soil is a net CO 2 sink (Lohila et al, 2011;Minkkinen et al, 2002). However, for two drained peatland forests, of different age and different nutrient supply, Dunn et al (2007) and Lohila et al (2007) found an annual NEE close to zero (+84 and −58 g C m −2 a −1 ).…”
Section: Annual Co 2 Exchangementioning
confidence: 98%
“…Some short-term studies conclude that peatland ecosystems drained for forestry are net CO 2 sinks (Lohila et al, 2011;Meyer et al, 2013;von Arnold et al, 2005). However, eddy covariance measurements over a boreal drained forest in central Sweden show considerable net CO 2 loss over 2 measurement years (Lindroth et al, 1998), while other studies determined net CO 2 exchange close to zero (Dunn et al, 2007;Lohila et al, 2007).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Before using the CoupModel, it was calibrated on high‐resolution datasets collected at the Skogaryd research station during 2007–2009. This included net radiation, soil surface heat flow, soil temperature, soil water content, water table depth, net ecosystem exchange of CO 2 (NEE), and N 2 O emissions (He, Jansson, Svensson, Meyer, et al., ; He, Jansson, Svensson, Björklund, et al., ; Meyer et al., ). The model was also calibrated with tree‐ring data, extending the period modeled to cover the spruce trees' entire lifespan (He, Jansson, Svensson, Björklund, et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately, 10% of the global AFOLU emissions are from drained peatlands. Of the world's peatlands, 10%–20% have been drained for agriculture or forestry purposes (FAO, ) causing them to be identified as GHG emission hotspots (Couwenberg et al., ; Davidson & Janssens, ; Meyer et al., ). The importance of drained peatlands has also been shown by the Swedish National Inventory Reporting (NIR) to the UN climate convention (UNFCCC), which calculated that they have emissions of 10 Tg CO 2 eq/year, which is almost as high as automobile emissions of 17 Tg CO 2 eq/year.…”
Section: Introductionmentioning
confidence: 99%
“…Lakes and bogs as well as agricultural fields are scattered throughout the region. Such a fragmented landscape has historically been formed due to farming and rural development [19]. …”
Section: Study Areamentioning
confidence: 99%